2013
DOI: 10.5901/mjss.2013.v4n11p159
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors Influencing eWOM

Abstract: Many studies demonstrated that Internet penetration and time spent online increased considerably in Turkey. However, there are not enough studies focusing on users attitudes towards e-Word of Mouth. E-Word Of Mouth is seen as more credible than other marketing communications since it comes directly from other consumers. eWOM shows high accessibility compared to traditional WOM, therefore its tools such as online recommendations, reviews or product ratings, are used more often and it makes eWOM more powerful. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
1
9
0
5
Order By: Relevance
“…Source credibility refers to consumers' overall perception regarding the credibility of an eWOM source rather than the content of the message. Source credibility is considered to be a basic factor, which helps individuals to judge eWOM communications (Akyuz 2013). The evaluation of a source is often made in terms of expertise, trustworthiness, credentials and attractiveness.…”
Section: Source Credibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Source credibility refers to consumers' overall perception regarding the credibility of an eWOM source rather than the content of the message. Source credibility is considered to be a basic factor, which helps individuals to judge eWOM communications (Akyuz 2013). The evaluation of a source is often made in terms of expertise, trustworthiness, credentials and attractiveness.…”
Section: Source Credibilitymentioning
confidence: 99%
“…The evaluation of a source is often made in terms of expertise, trustworthiness, credentials and attractiveness. Several studies have explored the relationship between source credibility and purchase intention (Akyuz 2013;Nekmat and Gower 2012;Yang et al 2015;Zhang et al 2014b). For example, by conducting surveys with 378 respondents from China, Yang et al (2015) found that information coming from a source perceived as credible positively affects intention to buy.…”
Section: Source Credibilitymentioning
confidence: 99%
“…Avoiding shopping from the Internet mostly depends on the risk problem (Hong & Yi, ) and due to having online shopping in a virtual space that contains more risks instead of face‐to‐face interactions, consumers begin a quest to search for more WOM messages (Kim & Song, ; Lee & Koo, ). This situation is the basis of eWOM being more accessible and powerful than the WOM (Akyüz, ). Unlike WOM, eWOM possesses an unprecedented speed of diffusion and enables multidirectional exchanges of information between communicators and receivers (Cheung & Thadani, ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Sadece anne sütü ile beslenmenin önemsendiği ülkelerde, çocuk hastalık ve ölümlerinin azaldığı ve bunun tek başına etkili bir faktör olduğu belirtil-mektedir. [8][9][10] Emzirme, bebeğin gereksinimlerini anlamada ve psikososyal-biyolojik gelişimini sağlamada en doğal ve etkili yol olmuştur. Doğumun ilk dakikalarında ten tene temas ile başlayan emzirme, bebeğin kendini güvende ve tanıdık bir ortamda hissetmesine neden olacak ve ilerleyen yaşamında öz güveni yüksek bir birey olmasını sağlayacaktır.…”
unclassified